Role of organics on the purification process of zinc sulfate solution and inhibition mechanism. (30th August 2019) - Wang, Tian; Lin, Guo; Gu, Likun; Hu, Tu; Xie, Tingfang; Qu, Hongtao; Wang, Shixing; Zhang, Libo; Cheng, Song; Liu, Jian; Di, Haokai
Abstract: The effects of organics (tannic acid and gelatin) on the removal of Cu 2+, Cd 2+, Co 2+ and Ni 2+ by metal zinc powder and electric furnace zinc powder were studied. The results indicated that the removal percent of Cu 2+, Cd 2+, Co 2+ and Ni 2+ was reduced by 13.74–48.52 percentages under adding gelatin. The removal percent of Cu 2+, Co 2+ and Ni 2+ was reduced by 6.03–59.32 percentages under adding tannic acid. However, the addition of tannic acid can increase the removal percent of Cd 2+ by 7.4–16.73 percentages. The wettability results indicated that the addition of tannic acid or gelatin to the solution leaded to poor wettability between the zinc powders and the solution. XRD and SEM-EDS of purified slag suggested that the inhibition mechanism of purification process was that the zinc powders in the solution were wrapped by organics. The amount of effective zinc powder was reduced to cause a decrease in impurity ions removal efficiency.